The Role and Impact of Marketing Content on Consumer Purchase Decisions: A Feasibility Study in The E-Commerce Sector - Nuryanti Nuryanti; Mildawati Mildawati; Andi Muhammad Afsar; Hasni Hasni (Management Department Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the role and impact of marketing content on consumer purchasing decisions in the context of e-commerce business feasibility studies. A descriptive qualitative approach was used, employing thematic analysis on seven students from the 2022 Sharia Accounting cohort who actively use e-commerce platforms. Data were collected through structured interviews based on five aspects of marketing content (informativeness, entertainment, credibility, personalization, and visual appeal) and the five stages of consumer purchasing decisions. The results indicate that marketing content plays a crucial role in influencing all stages of the purchasing process, from need recognition to post-purchase behavior. Informative and credible content builds trust, while entertaining, personalized, and visually appealing content enhances interest and engagement. These findings affirm that marketing content is not merely a promotional tool but also a key indicator in digital business feasibility studies, as it reflects product value, gauges market response, and supports operational and financial planning. This research offers practical contributions for e-commerce entrepreneurs in designing effective content strategies and academic contributions to the development of digital marketing studies within the scope of business feasibility.Keywords: Business Feasibility Study, E-Commerce, Generation Z, Marketing Content, Purchasing Decision